Interruption of mitochondrial symbiosis is associated with the development of osteoporosis - Zhang, Haoling; Zhao, Rui; Wang, Xuemei; Qi, Yaqian; Sandai, Doblin; Wang, Wei; Song, Zhijing; Liang, Qiudong (Frontiers in Endocrinology, 2025)
Mitochondria maintain bacterial traits because of their endosymbiotic origins, yet the host cell recognizes them as non-threatening since the organelles are compartmentalized. Nevertheless, the controlled release of mitochondrial components into the cytoplasm can initiate cell death, activate innate immunity, and provoke inflammation. This selective interruption of endosymbiosis as early as 2 billion years ago allowed mitochondria to become intracellular signaling hubs. Recent studies have found that the interruption of mitochondrial symbiosis may be closely related to the occurrence of various diseases, especially osteoporosis (OP). OP is a systemic bone disease characterized by reduced bone mass, impaired bone microstructure, elevated bone fragility, and susceptibility to fracture. The interruption of intra-mitochondrial symbiosis affects the energy metabolism of bone cells, leads to the imbalance of bone formation and bone absorption, and promotes the occurrence of osteoporosis. In this paper, we reviewed the mechanism of mitochondrial intersymbiosis interruption in OP, discussed the relationship between mitochondrial intersymbiosis interruption and bone marrow mesenchymal stem cells, osteoblasts and osteoclasts, as well as the inheritance and adaptation in the evolutionary process, and prospected the future research direction to provide new ideas for clinical treatment.